Simplifying
3X + 10 = 6X + 40
Reorder the terms:
10 + 3X = 6X + 40
Reorder the terms:
10 + 3X = 40 + 6X
Solving
10 + 3X = 40 + 6X
Solving for variable 'X'.
Move all terms containing X to the left, all other terms to the right.
Add '-6X' to each side of the equation.
10 + 3X + -6X = 40 + 6X + -6X
Combine like terms: 3X + -6X = -3X
10 + -3X = 40 + 6X + -6X
Combine like terms: 6X + -6X = 0
10 + -3X = 40 + 0
10 + -3X = 40
Add '-10' to each side of the equation.
10 + -10 + -3X = 40 + -10
Combine like terms: 10 + -10 = 0
0 + -3X = 40 + -10
-3X = 40 + -10
Combine like terms: 40 + -10 = 30
-3X = 30
Divide each side by '-3'.
X = -10
Simplifying
X = -10
Answer:
4C0m430 + 4C1m331 + 4C2m232 + 4C3m133 + 4C4m034
Step-by-step explanation:
Pascales triangle useing codes THis is also equivlent to x4 + 12x3 + 54x2 + 108x + 81
the problem isnt that hard. you need to do the distributive property or FOIL with (m+3) four different times. The answer would be
M^4 + 12M^3 +54M^2 +108M +81
A: 18
B: 24
C: 12
D: 16